Investigating Accessibility and Availability of Therapeutic Opioids in Surabaya, Indonesia - Maryono, Khaliq; Hermansyah, Andi; Wijaya, I Nyoman (Faculty of Medicine Universitas Sebelas Maret, 2025)
Introduction: A significant global disparity exists in access to opioid analgesics for pain management, with high-income countries (HICs) responsible for over 90% of global opioid consumption. In stark contrast, low- and middle-income countries (LMICs)—which are home to 90% of the world's population—account for less than 10% of this consumption. Despite a pressing clinical need among groups such as cancer patients, surgical cases and other individuals suffering from pain, access to opioids remains severely restricted. This study aims to investigate whether similar gaps in access and utilization exist in Surabaya by analyzing the availability and consumption data of therapeutic opioids.Methods: A retrospective observational study was carried out utilizing secondary data collected from Surabaya, Indonesia, during April to May 2025. The data were extracted from Kimia Farma (KF) and SIPNAP provided by the local health office, covering the years 2022 to 2024. All opioid agonists distributed by the KF and reported as utilized in healthcare facilities in Surabaya were included in the analysis. Descriptive analysis of the data was conducted using Microsoft Excel to identify trends in opioid distribution and usage over time, with a particular emphasis on patterns of decline and their potential contributing factors.Results: During the study period, a total of 21 different types of opioids were identified. Overall, distribution trends experienced a modest increase of 6%, while utilization trends showed a slight decrease of 2%. Notable declines were observed in several opioids, particularly in hydromorphone, oxycodone, oral codeine formulations, and fentanyl patches. Across various healthcare settings, opioid use rose in clinics (7%) and hospitals (4%), but saw a significant drop in pharmacies (19%). This indicates an uneven accessibility to opioids and persistent gaps in availability and usage across different service levels in Surabaya.Conclusion: While opioid use in hospitals and clinics remains relatively stable, there has been a significant decrease in access to several essential opioids at the distribution level. If this trend continues, it is likely that usage will decline further, thereby limiting access to adequate pain management. Urgent policy interventions are necessary— including regulatory refinement, enhanced training for healthcare workers, and improved product availability—to restore a favorable balance between distribution and usage. Strengthening these areas is critical to ensuring equitable access to opioid analgesics and upholding the right to adequate pain relief.